Exploring fake communication news through Facebook - Sabri, Rizwan; Kamaruddin, Azlina (2018)
The researchers conduct a study to explore about fake communication in new media scenario, but we eliminate focus on the issue of rumors. The research aims are (i) to identify the form of posting rumors available in Facebook; (ii) to explore the incurred though Facebook actions of Facebook users to post rumors; and (iii) to analyze the content of Facebook users response through comments on posts though Facebook. The methodology that we prefer to use is semi-structured interview and qualitative content analysis. The root reason for carrying out semi-structured interviews is because we are interested to understand the forms of posting rumours and actions taken by the general public about the issue of fake communication. Meanwhile, for qualitative content analysis, we will select Facebook which is focusing on internet users comment’ about fake communication issue. The expectation for research finding is to enlarge literature based on fake communication news and its’ relation with Facebook.